Compact triple‐band antenna for WiMAX and WLAN applications. Issue 7 (1st March 2014) - Verma, S.; Kumar, P.
Abstract : A triple‐band planar antenna with a compact radiator is proposed for 2.3/3.5/5.5 GHz WiMAX and 5.2/5.8 GHz WLAN applications simultaneously. The proposed antenna consists of an inverted‐L (IL)‐shaped radiating element and a parasitic element in the ground plane to generate three resonant modes for triple‐band operations. Each of the three resonant bands can be tuned separately to cover other wireless applications also. Owing to the coupling of the IL‐driven element and the parasitic element, a compact radiator of 10 × 17.3 mm 2 is realised for triple‐band operations. Some key parameters affecting the antenna performance have been analysed using computer simulations. To validate the simulation results, the prototypes of the proposed antenna are fabricated on an inexpensive FR‐4 substrate and tested. Good radiation characteristics of the proposed antenna have been obtained. The simulated and measured results are in good agreement.